An Examination of Mindfulness Skills in terms of Affect Tolerance among Individuals with Elevated Levels of Health Anxiety - O’Bryan, Emily M. (Anxiety Stress Coping, 2018)
BACKGROUND AND OBJECTIVES. Affect tolerance factors, including anxiety sensitivity, intolerance of uncertainty, and emotional distress tolerance, have been implicated in the exacerbation of health anxiety. Therefore, identifying methods to improve affect tolerance in health anxious populations is imperative. Despite the link between mindfulness and greater affect tolerance in non-clinical populations, no work has examined the role of mindfulness skills in terms of affect tolerance among individuals with elevated health anxiety. The aim of the current study was to examine the unique contribution of mindfulness skills in terms of distress tolerance, anxiety sensitivity, and intolerance of uncertainty. METHODS. Participants were 218 undergraduates with clinically-elevated levels of health anxiety (75.7% female; M(age) = 19.53, SD = 3.16, Range = 18-45) who completed self-report measures for course credit. RESULTS. Findings indicated that, after controlling for theoretically relevant covariates, greater acting with awareness, nonjudgment, and nonreactivity were uniquely associated with greater distress tolerance, and greater non-reactivity was associated with lower levels of intolerance of uncertainty. Though none of the mindfulness skills emerged as specific individual predictors of anxiety sensitivity, these skills collectively accounted for unique variance in anxiety sensitivity. CONCLUSIONS. These findings suggest that mindfulness skills may be helpful in targeting affect tolerance factors among individuals with elevated health anxiety.